Improvement in device performance of double-pass concentric circular mass exchanger with an idealized membrane inserted. - Ho, Chii-Dong (Journal of Applied Science and Engineering)
A new design of the concentric circular mass exchanger with an idealized tubular membrane inserted is investegated theoretically. The recycle-effect concept is introduced to enhance the mass transfer rate of the double-pass concentric circular mass exchanger. A theoretical mathematical model is developed to predict the concentration distribution and mass transfer efficiency. The analytical solution is obtained by using a linear superposition of an asymptotic solution and a homogeneous solution with the orthogonal expansion technique in terms of power series. The theoretical results show that a considerable mass-transfer efficiency improvement is achievable by applying the double-pass design with the recycle-effect concept into a single-pass circular mass exchanger under constant wall mass fluxes.